2008
DOI: 10.1007/s00455-008-9161-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral-motor Dysfunction at 10 Months Corrected Gestational Age in Infants Born Less Than 37 Weeks Preterm

Abstract: Feeding difficulties are common in preterm infants. These may be associated with inadequate dietary intake, poor growth, and parental anxiety. Oral-motor dysfunction has been observed in preterm infants during sucking and the early stages of weaning but has not been rigorously studied in later infancy when eating a range of food consistencies. We aimed to establish if oral-motor dysfunction during feeding occurs in preterm infants in later infancy and to explore the relationships with specific neonatal risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
(37 reference statements)
0
8
0
5
Order By: Relevance
“…These visits may have greater importance for premature infants who are at increased risk for medical and neurodevelopmental sequelae. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] There are few studies assessing adherence with health supervision visits in the general pediatric population and fewer in high-risk populations. According to Medical Expenditure Survey data, infants were found to be 83% adherent with the age-specific number of visits recommended by the AAP.…”
mentioning
confidence: 99%
“…These visits may have greater importance for premature infants who are at increased risk for medical and neurodevelopmental sequelae. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] There are few studies assessing adherence with health supervision visits in the general pediatric population and fewer in high-risk populations. According to Medical Expenditure Survey data, infants were found to be 83% adherent with the age-specific number of visits recommended by the AAP.…”
mentioning
confidence: 99%
“…These visits may have greater importance for premature infants who are at increased risk for medical and neurodevelopmental sequelae. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] There are few studies assessing adherence with health supervision visits in the general pediatric population and fewer in high-risk populations. According to Medical Expenditure Survey data, infants were found to be 83% adherent with the age-specific number of visits recommended by the AAP.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Studies have suggested an association between a younger gestational age and greater risk of the development of oral motor disorders. Thus, the intervention of a speech therapists is important to the prevention and rehabilitation of correlate abnormalities and should be maintained throughout the follow up of cases during the introduction of other food consistencies 16,17 .…”
Section: Figure 2 -Most Frequent Diagnostic Hypotheses Given By Physimentioning
confidence: 99%